2002
DOI: 10.1021/ic0106726
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Sb(OC6H3Me2-2,6)3 and Sb(OEt)5·NH3: The First Authenticated Monomeric Sb(OR)n (n = 3, 5)

Abstract: The first monomeric antimony alkoxides, Sb(OC(6)H(3)Me(2))(3) (1) and Sb(OEt)(5) x NH(3) (2), have been crystallographically characterized. The former adopts a trigonal pyramidal geometry, while the latter is octahedral about antimony; hydrogen bonding between NH(3) and SbOEt groups in Sb(OEt)(5) small middle dotNH(3) creates a one-dimensional lattice arrangement. Reaction of pyridine with SbCl(5) in EtOH/hexane yields the salt [Hpy(+)](9)[Sb(2)Cl(11)(5)(-)][Cl(-)](4) (3), which has also been crystallographica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 30 publications
(35 reference statements)
0
20
0
Order By: Relevance
“…In summary, ½j 4 -NðCH 2 Ar Bu t 2 OÞ 3 Sb may be readily obtained via reaction of Sb(OEt) 3 (9), Sb1-O13 1.972(9), Sb1-O11 1.997(9), Sb1-N1 2.207(11), Sb2-O1 1.970(9), Sb2-O2 1.954(9), Sb2-O102 1.957(9), Sb3-O2 1.907(9), Sb3-O3 1.950(9), Sb3-O31 1.968(10), Sb3-O32 1.984(10), Sb3-O33 1.993(10), Sb3-N3 2.243(11), Sb4-O3 1.976(9), Sb4-O4 1.960(10), Sb4-O102 1.980(9), Sb5-O4 1.929(9), Sb5-O5 1.900(9), Sb5-O51 1.981(9), Sb5-O52 1.987(9), Sb5-O53 1.969(11), Sb5-N5 2.209(11), Sb6-O5 1.936(9), Sb6-O6 1.944(9), Sb6-O101 1.959(9), Sb7-O6 1.930(9), Sb7-O7 1.913(9), Sb7-O71 2.008(10), Sb7-O72 1.967(10), Sb7-O73 1.984(10), Sb7-N7 2.189(11), Sb8-O7 2.042(9), Sb8-O8 1.963(9), Sb8-O101 1.951(9). ½j 4 -NðCH 2 Ar Bu t 2 OÞ 3 SbðOHÞ 2 , and f½j 4 -NðCH 2 Ar Bu t 2 OÞ 3 -Sb V Og 4 fSb III 4 O 6 g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, ½j 4 -NðCH 2 Ar Bu t 2 OÞ 3 Sb may be readily obtained via reaction of Sb(OEt) 3 (9), Sb1-O13 1.972(9), Sb1-O11 1.997(9), Sb1-N1 2.207(11), Sb2-O1 1.970(9), Sb2-O2 1.954(9), Sb2-O102 1.957(9), Sb3-O2 1.907(9), Sb3-O3 1.950(9), Sb3-O31 1.968(10), Sb3-O32 1.984(10), Sb3-O33 1.993(10), Sb3-N3 2.243(11), Sb4-O3 1.976(9), Sb4-O4 1.960(10), Sb4-O102 1.980(9), Sb5-O4 1.929(9), Sb5-O5 1.900(9), Sb5-O51 1.981(9), Sb5-O52 1.987(9), Sb5-O53 1.969(11), Sb5-N5 2.209(11), Sb6-O5 1.936(9), Sb6-O6 1.944(9), Sb6-O101 1.959(9), Sb7-O6 1.930(9), Sb7-O7 1.913(9), Sb7-O71 2.008(10), Sb7-O72 1.967(10), Sb7-O73 1.984(10), Sb7-N7 2.189(11), Sb8-O7 2.042(9), Sb8-O8 1.963(9), Sb8-O101 1.951(9). ½j 4 -NðCH 2 Ar Bu t 2 OÞ 3 SbðOHÞ 2 , and f½j 4 -NðCH 2 Ar Bu t 2 OÞ 3 -Sb V Og 4 fSb III 4 O 6 g.…”
mentioning
confidence: 99%
“…Dacron Ò , Mylar Ò and Terylene Ò ) [1][2][3], and as precursors for the deposition of thin films of Sb 2 O 3 and Sb 6 O 13 [4]. The coordination chemistry of antimony alkoxide and aryloxide compounds is, however, complex, as illustrated by the structural variations that are observed for [Sb(OMe) 3 ] n [5], [Sb(OPr i ) 3 ] 2 [6], [Sb(OSiMe 3 ) 3 ] 2 [7,8], Sb(OC 6 H 3 -2,6-Me 2 ) 3 [9], and [Sb 2 (OCH 2 CH 2 O) 3 ] n [10]. As part of an effort to investigate the reactivity of well-defined antimony aryloxide compounds, we recently described the first application of the tris(phenol)amine N(o-C 6 H 4 OH) 3 to antimony chemistry [11].…”
mentioning
confidence: 99%
“…Sb(OEt) 3 and Sb(OEt) 5 ؒNH 3 were prepared by published procedures. 3,17 Hexane and toluene were distilled over CaH 2 prior to use. All reactions were carried out in an inert atmosphere (N 2 and Ar) using a dry-box and Schlenk-line techniques.…”
Section: Experimental General Proceduresmentioning
confidence: 99%
“…Our interest in the chemistry of antimony oxide-based sensors and the chemical vapour deposition (CVD) of such materials 1,2 has caused us to focus our attention on the synthesis of precursors for these procedures. In this regard, we have recently reported on the chemistry of monomeric antimony alkoxides 3 and carbamates, 4 the latter in particular proving to be excellent CVD precursors. Other classes of compound which are widely exploited in the CVD of oxide films are homoleptic metal β-diketonates, M(β-dk) n , and the heteroleptic complexes which also incorporate alkoxide ligands, M(β-dk) n (OR) m .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, chemists have been focusing on synthesis, fine-tuning, and structural characterization of new metallocalixarenes for their potential applications in homogeneous catalysts and novel materials with transition metals and heavy main group elements [4][5][6][7]. While the bismuth complex with aryloxides and alkoxides demonstrated their extensive applications in catalysts, medicine, superconductor and ferroelectric materials [8][9][10], the recent work by Hanna et al showed the different kind of binding mode of bismuth Calixarenes complexes and their chemistry properties are quite different from that of their lighter congeners [2,[11][12][13][14][15]. Previous studies have shown that most of the metal-calix [4] arene system usually binds in a tetradentate, cone-like fashion with square pyramidal complex [16,17].…”
Section: Introductionmentioning
confidence: 99%